2016
DOI: 10.1097/sap.0000000000000777
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the Musculus Uvulae to Velopharyngeal Closure Quantified With a 3-Dimensional Multimuscle Computational Model

Abstract: The convexity of the dorsal surface of the velum is critical for normal velopharyngeal (VP) function and is largely attributed to the levator veli palatini (LVP) and musculus uvulae (MU). Studies have correlated a concave or flat nasal velar surface to symptoms of VP dysfunction including hypernasality and nasal air emission. In the context of surgical repair of cleft palates, the MU has been given relatively little attention in the literature compared with the larger LVP. A greater understanding of the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…The observations from the present study agree with prior studies suggesting that the musculus uvulae are preserved to some degree in those with repaired cleft palate (F#x00E1;ra and Dvor#x00E1;k, 1970;Calnan, 1954). Inouye et al (2016) recently evaluated the contribution of the musculus uvulae to velopharyngeal closure using a computational model that simulates multiple scenarios of muscle abnormalities. The authors observed that with a 100% activation level of the musculus uvulae with low levels of levator veli palatini activation, the musculus uvulae had the capacity to preserve normal velopharyngeal closure.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The observations from the present study agree with prior studies suggesting that the musculus uvulae are preserved to some degree in those with repaired cleft palate (F#x00E1;ra and Dvor#x00E1;k, 1970;Calnan, 1954). Inouye et al (2016) recently evaluated the contribution of the musculus uvulae to velopharyngeal closure using a computational model that simulates multiple scenarios of muscle abnormalities. The authors observed that with a 100% activation level of the musculus uvulae with low levels of levator veli palatini activation, the musculus uvulae had the capacity to preserve normal velopharyngeal closure.…”
Section: Discussionsupporting
confidence: 90%
“…Inouye et al (2016) recently evaluated the contribution of the musculus uvulae to velopharyngeal closure using a computational model that simulates multiple scenarios of muscle abnormalities. The authors observed that with a 100% activation level of the musculus uvulae with low levels of levator veli palatini activation, the musculus uvulae had the capacity to preserve normal velopharyngeal closure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Truly passive mechanical properties of airway tissue would have to be estimated using mechanical testing, although some studies have also proposed to obtain the same using MRE with respiratory gating (Cheng et al, 2011). Activation of the levator veli palitini and musculus uvulae has been studied previously using CSM (Inouye et al, 2016) and the same would have to be considered in a future study to model flow-induced palate movement during wakefulness. Modeling the same would necessitate MR images with higher image contrast between individual tissue structures (Perry et al, 2014).…”
Section: Discussionmentioning
confidence: 99%